2019
DOI: 10.1038/s41598-019-55641-6
|View full text |Cite|
|
Sign up to set email alerts
|

Plasma activity of Thioredoxin Reductase as a Novel Biomarker in Gastric Cancer

Abstract: Gastric cancer (GC) is one of the leading malignancies around the world. Identification of novel and efficient biomarkers for GC diagnosis and evaluation of therapeutic efficiency could improve the therapeutic strategy in future clinical application. This study aims to evaluate the levels of plasma thioredoxin reductase (TrxR) activity in GC patients to confirm its validity and efficacy in GC diagnosis and evaluation of therapeutic efficiency. 923 cases were enrolled in the current study. In the group of GC pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 49 publications
(65 reference statements)
0
17
0
Order By: Relevance
“…[157] TRXR activity is significantly higher in the plasma of gastric cancer patients compared to healthy controls. [180] Hepatocellular carcinoma TRX expression is overexpressed in HCC compared to the control group.…”
Section: Tumor Typementioning
confidence: 99%
“…[157] TRXR activity is significantly higher in the plasma of gastric cancer patients compared to healthy controls. [180] Hepatocellular carcinoma TRX expression is overexpressed in HCC compared to the control group.…”
Section: Tumor Typementioning
confidence: 99%
“…Thioredoxin reductase (TrxR) is a NADPH-dependent dimeric selenide containing FAD domains. Numerous studies have shown that levels of TrxR are significantly higher than those of CEA and CA19-9 in malignant diseases such as breast, lung, and colorectal cancers 34 , 58 . In addition, TrxR has shown great therapeutic value in malignant diseases such as renal and lung cancer, and the combined sensitivity of TrxR compared with conventional tumor markers alone seems to be superior 34 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies suggested that TrxR indicates higher levels of abnormally proliferating cells, and may have a superior diagnostic efficacy than other conventional tumor markers. In addition, TrxR activity is rapidly downregulated after chemotherapy in non-small cell lung cancer (NSCLC), gastric cancer, and breast cancer [33][34][35] . Previous studies consistently demonstrated that TrxR has potentially high value for clinical diagnosis and assessment of therapeutic efficacy.…”
mentioning
confidence: 99%
“…As both Trx and TrxR1 have been reported to be upregulated in numerous human cancer types, including leukemia, lung cancer, breast cancer and colorectal cancer among others, and be associated with increased tumor growth, drug resistance and poor patient prognosis, the thioredoxin system has been recognized as an attractive target for anticancer drug development (4,(6)(7)(8)(9)(10)40). This system plays a role in maintaining H 2 O 2 levels in cells via the conversion of H 2 O 2 to H 2 O. Trx contains two adjacent thiols in its reduced form that are converted to a disulfide bond in the oxidized form (39).…”
Section: Discussionmentioning
confidence: 99%
“…Mammalian thioredoxin (Trx) reductase 1 (TrxR1) is a selenoprotein that functions to maintain redox homeostasis in cells via transferring electrons from NADPH to its substrate Trx (4,5). Both Trx and TrxR1 are reported to be upregulated in CRC cells and have been associated with poor prognosis and resistance to chemotherapy (6)(7)(8)(9). Increasing evidence has suggested that TrxR1 is involved in multiple steps of tumorigenesis (10)(11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%